Preparation method of nanocrystalline strip and nanoparticles based on gas-phase driving and liquid rolling
Through the gas-phase driving and liquid rolling method, the problems of uneven size and poor dispersion of nanoparticles are solved, and the uniformity and high performance of nanocrystal particles are achieved, and the demands of hard magnetic nanoparticles in multiple high-tech fields are met. .
Patent Information
- Application Number
- CN202411546699.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-01
AI Technical Summary
In the prior art, when preparing hard magnetic nanoparticles, it is difficult to achieve mass production, and the nanoparticles are uneven in size and poor in dispersion, which affects their performance.
Using gas-phase driving and liquid rolling methods, nanocrystalline belts are prepared through alloy melting, casting, rolling, crystallized thin strip collection, nanocrystallation diffusion heat treatment, heat treatment crushing treatment and chemical physics-driven particle separation. Materials and nanoparticles.
It has achieved good size uniformity and dispersion of nanocrystal particles, excellent performance, and can meet the needs of hard magnetic nanoparticles in the fields of information storage, stealth coating and electromagnetic shielding.
Smart Images

Figure CN119480408A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnetic materials, and in particular relates to a preparation method of nanocrystalline strips and nanoparticles based on gas phase driving and liquid rolling. Background Art
[0002] With the rapid progress of modern science and technology, nanoscience has shown great potential and application prospects in many fields such as materials science, information technology, biomedicine, etc. Magnetic nanoparticles, as an important branch of nanomaterials, have received extensive attention and research in data storage, biomedicine, catalysts, etc. due to their unique physical and chemical properties, such as superparamagnetism, high specific surface area, and excellent biocompatibility.
[0003] There is a great demand for hard magnetic nanoparticles in the fields of information storage, stealth coatings, electromagnetic shielding, etc. Hard magnetic nanoparticles have shown excellent application potential in the fields of information storage, stealth coatings and electromagnetic shielding. In information storage, they have become key materials for improving storage density and speed by virtue of their high magnetic susceptibility and stability; in the field of stealth coatings, by adjusting their electromagnetic properties, broadband stealth is achieved and target concealment is enhanced; and in electromagnetic shielding, efficient wave absorption and attenuation capabilities are used to provide reliable protection for electronic equipment. These characteristics together establish the important position of hard magnetic nanoparticles in many high-tech fields.
[0004] There are various preparation processes for magnetic nanocrystalline particles, including chemical methods, physical methods, and biological methods. These methods have their own advantages and disadvantages. Patent CN115196954B is to obtain an amorphous thin film on a single crystal silicon substrate by a sol-gel process spin coating method. This method cannot achieve mass production. Patent US20110244271 A1 is to flow the molten alloy directly into the roll gap through a water nozzle, and obtain an amorphous thin strip after a relatively small casting force, and obtain hexagonal ferrite magnetic powder after reheating and crystallization annealing. The molten alloy flows through a long distance to the roll gap in the form of a liquid column. The liquid column is cooled unevenly inside and outside, resulting in huge structural fluctuations, and its heat treatment process is crystallization annealing. Because its amorphous structure has large fluctuations and is not heated evenly during the heating process, the crystallization size is uneven during this crystallization process. Summary of the invention
[0005] In response to the problems in the prior art, the present invention provides a method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling, through which the nanocrystalline particles obtained are uniform in size, good in dispersion, and excellent in performance, which can meet the needs of hard magnetic nanoparticles in the fields of information storage, stealth coatings, electromagnetic shielding, etc.
[0006] The technical solution of the present invention is: A method for preparing nanocrystalline strips and nanoparticles based on gas phase driving and liquid rolling comprises the following steps: Step (1) Alloy melting Smelt the alloy according to the set composition. Use high-purity alumina or Pt-Rh alloy in the smelting crucible. Heat it to 1300-1450℃ and keep it warm for 2-3 hours. After the alloy powder is melted, add 1 / 3 of the weight of the melted powder into the alloy powder briquette. After it is completely melted, stir it for more than 30 minutes to promote uniform distribution. Step (2) Pouring After the alloy is melted and the crucible is preheated, the gate is heated online, and the molten alloy is poured into the distribution nozzle by using the method of water gate flow storage, small diameter gate flow control and spray deposition ring spraying. The molten alloy is introduced through the nozzle down nozzle, and the liquid is dispersed into droplets through the spray deposition ring. The droplets enter the double-roll gap for rolling and cooling; Step (3) Rolling During the rolling process, when the molten liquid is poured, the double-roller surface speed is 2-10m / s, and the double-roller arch frame moves back and forth along the axial direction as a whole, with a moving speed of 0~20mm / s, which is convenient for adjusting the heat exchange capacity of the roller surface; constant casting and rolling force control is adopted, and the sum of the casting and rolling forces on both sides is 10-100kN; the diameter of the casting roller is 200-400mm, the roller width is 110-350mm, and the roller surface convexity is +10~25μm. According to the matching of the roller surface material and the casting roller stiffness, after the casting and rolling force is applied, the roller gap is balanced; the cooling water flux of the casting roller is 30-100m 3 / h; the casting roll power drive is directly connected to the servo motor to achieve synchronous dynamic adjustment; the width of the crystallized strip is controlled to be 5~40mm; Step (4) Collection of crystallized thin strips The casting machine outlet is designed with a multi-channel collecting bin to distinguish and collect the pouring, genuine product and cast residue separately. The cast residue bin is equipped with heat insulation materials to isolate it from the genuine product bin to avoid annealing influence. Step (5) Nanocrystallization diffusion heat treatment Take the genuine crystallized thin ribbon and carry out nano-crystallization diffusion heat treatment in a strong air circulation muffle furnace to make the boron diffuse more evenly to the grain boundary, which is convenient for the subsequent chemical and physical driven particle separation; Step (6) Heat-treated strip material is crushed The ball mill is mixed with liquid nitrogen for ball milling. The grinding ball is made of zirconium oxide or titanium oxide. Liquid nitrogen is added in a ratio of 1:2 for wet grinding and refining. The diameter distribution of the ball milled particles is controlled to be 0.1~0.5μm. The over-fine and over-coarse powders are removed and recycled. Step (7) Chemical and physical driven particle separation The ball mill particles are subjected to the first pickling, the pickling solution is 1% acetic acid, the mass ratio of powder particles to pickling solution is 1:2~4, and the pickling is stirred at 70°C for 5~10 minutes. After removing the upper liquid, the primary pickling powder is obtained, and the broken nanoparticles are removed; the primary pickling mixture is subjected to the second pickling, the pickling solution is 5% acetic acid, the mass ratio of powder particles to pickling solution is 1:5~10, and the pickling is stirred at 85°C for 100-150 minutes with sufficient stirring; then after repeated centrifugal washing and drying, the magnetic nanoparticles are obtained and collected.
[0007] Furthermore, in the above-mentioned method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling, the set composition in step (1) is (Fe2O3) by weight percentage. a (BaCO3) b (SrCO3) c (H3AlO3) d (H3BO3) e (CoO) f (TiO2) g (Bi2O3) h (Nd2O3) i , where the mass fraction is a: 10~30%; b: 30~40% or 1~6%; c: 1~5% or 30~40%; d: 0~3%; e: 10~25%; f: 0~1%; g: 0~1%; h: 0~5%; i: 0~5%.
[0008] Furthermore, in the above-mentioned method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling, in step (2), a preheater is used to preheat a water nozzle, wherein the water nozzle is made of alumina or Pt-Rh, the preheating temperature is 1200-1300°C, the pouring water nozzle aperture is 1-3mm, the liquid level height is controlled at 100-180mm, a weighing device is used to measure the amount of molten alloy, and to control the amount of molten alloy poured in and out; the water nozzle is located in the middle of the injection deposition ring, the water nozzle is aligned with the center line of the injection deposition ring, the lower plane of the water nozzle is parallel to the lower plane of the injection deposition ring, the injection deposition ring is 200-240mm away from the roller gap, the injection deposition ring slit width is 1-2mm, the annular slit inclination angle is 45°, the focal length is 40mm, and the injection pressure is 0.3-0.4MPa.
[0009] Furthermore, in the above-mentioned method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling, the casting roller material in step (3) is beryllium copper or chrome-plated mold steel, wherein the beryllium copper roller sleeve coating thickness is 50-250μm, the mold steel chrome-plated sleeve coating thickness is 10-50μm, the coating polishing roughness requirements are ≤Ra0.8μm, and the hardness is ≥60HRC.
[0010] Furthermore, in the above-mentioned method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling, the heat treatment process in step (5) is as follows: the air flow velocity is 2-3 m / s, the crystallized strip is placed on a multi-unit shelf using a 304 stainless steel tray, and the thickness of a single tray does not exceed 10 mm; the furnace entry temperature is not higher than 100°C, and the temperature is raised to 550~790°C at a rate of ≤10°C / min and maintained at this temperature for 0.5-5h for heat treatment.
[0011] Furthermore, in the above-mentioned method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling, the nanoparticles prepared by this preparation method are single crystals, more than 85% of the particles are undamaged, the damaged volume is ≤10%, and the particle proportion is more than 95%.
[0012] Furthermore, the above-mentioned method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling has a particle size D80 of 8-10nm and 20-30nm in six aspects of strontium-based and barium-based nanoparticles prepared by the preparation method, a hexagonal prism structure, an aspect ratio of 1.2-1.8:1, and a magnetic induction of 35-80 A·m 2 / kg.
[0013] Advantages and beneficial effects of the present invention: 1. The present invention provides a method for efficient forming of less than 20 μm based on the process of liquid efficient rolling, which can form continuously and the obtained product is a uniform nano-crystallized thin strip; 2. The present invention adopts a double-roll liquid rolling process, which overcomes the problems of uneven cooling speed and shape fluctuations of the roller surface and free surface in the single-roll method, and creates a geometric basis for subsequent diffusion heat treatment, chemical and physical driven particle separation, spheroidization and other processes; 3. The present invention adopts a process combining spray dispersion and double-roll liquid rolling, which can apply a large rolling forming force during cooling, that is, high-temperature severe viscoplastic deformation, giving the nanocrystalline ribbon a short-range ordered huge free volume energy input, fully ensuring that the energy at each location of the nanocrystalline ribbon is high-energy and uniform during the forming process, and can meet the crystallization conditions during the rolling process, and then nucleate and grow. Because the nucleation amount at each point is uniform, its competitive growth is very uniform, so the size of the nanoparticles obtained is very uniform; 4. The present invention adopts a comprehensive separation method of physical metallurgy and chemical physics, and the product obtained on the basis of the above has distinct particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is a process flow chart of the present invention; Figure 2 TEM image of nanocrystalline particles prepared in Example 1 of the present invention; Figure 3 Schematic diagram of gas phase drive and liquid rolling process; In the figure, 1-water nozzle, 2-spray deposition ring, 3-casting roller. DETAILED DESCRIPTION
[0015] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention but cannot be used to limit the scope of the present invention.
[0016] The following embodiments are based on the preparation methods of gas phase driven and liquid rolling nanocrystalline strips and nanoparticles using the following method: Figure 1 The process flow is shown. Example 1
[0017] The present embodiment provides a method for preparing nanocrystalline strips and nanoparticles based on gas phase driving and liquid rolling, comprising the following steps: Step (1) Alloy melting Set the alloy composition by weight percentage to (Fe2O3) a (BaCO3) b (SrCO3) c (H3AlO3) d (H3BO3) e (CoO) f (TiO2) g (Bi2O3) h (Nd2O3) i , where the mass fractions are a: 30%; b: 30%; c: 5%; d: 2%; e: 25%; f: 1%; g: 1%; h: 3%; i: 3%; the melting crucible is made of high-purity alumina, heated to 1450°C for 3 hours, and then 1 / 3 of the weight of the molten powder is added to the alloy powder briquette after the alloy powder is melted; after it is completely melted, it is fully stirred for 40 minutes to promote uniform distribution; Step (2) Pouring After the alloy is melted and the crucible is preheated in place, the gate is heated online, and the molten alloy is poured into the distribution water outlet by using the method of water outlet flow storage, small diameter gate flow control and jet deposition ring injection, and the molten alloy is introduced through the water nozzle under the water outlet, and the liquid is dispersed into droplets through the jet deposition ring, and the droplets enter the roll gap of the double rollers for rolling and cooling; specifically, a preheater is used to preheat the water nozzle, wherein the water nozzle is made of alumina, the preheating temperature is 1300℃, the pouring water nozzle aperture is 2mm, the liquid level height is controlled at 150mm, and a weighing device is used to measure the amount of molten alloy, and the amount of molten alloy poured in and out is controlled; the water nozzle is located in the middle of the jet deposition ring, the water nozzle is aligned with the center line of the jet deposition ring, the lower plane of the water nozzle is parallel to the lower plane of the jet deposition ring, the distance between the jet deposition ring and the roll gap is 200mm, the slit width of the jet deposition ring is 2mm, the annular slit inclination angle is 45°, the focal length is 40mm, and the injection pressure is 0.3MPa; Step (3) Rolling Rolling process such as Figure 3 As shown, it includes a water nozzle 1, a spray deposition ring 2 and two casting rollers 3. When the molten liquid is poured, the double-roller roller surface rotates at a speed of 10m / s, and the double-roller arch frame moves back and forth along the axial direction as a whole, with a moving speed of 10mm / s, so as to facilitate the regulation of the heat exchange capacity of the roller surface; constant casting and rolling force control is adopted, and the sum of the casting and rolling forces on both sides is 100kN; the diameter of the casting roller is 300mm, the roller width is 200mm, and the roller surface convexity is ﹢15μm. According to the matching of the roller surface material and the casting roller stiffness, the roller gap is balanced after the casting and rolling force is applied; the casting roller material is beryllium copper chrome-plated, and the beryllium copper roller sleeve coating thickness is 100μm; the coating polishing roughness requirement is ≤Ra 0.8μm, and the hardness is ≥60HRC; the casting roller cooling water flux is 50m 3 / h; the casting roll power drive is directly connected to the servo motor to achieve synchronous dynamic adjustment; the width of the crystallized strip is controlled to be 30mm; Step (4) Collection of crystallized thin strips The casting machine outlet is designed with a multi-channel collecting bin to distinguish and collect the pouring, genuine product and cast residue separately. The cast residue bin is equipped with heat insulation materials to isolate it from the genuine product bin to avoid annealing influence. Step (5) Nanocrystallization diffusion heat treatment Take the genuine crystallized thin strip and carry out nano-crystallization diffusion heat treatment in an air-force circulation muffle furnace. The airflow velocity is 3m / s. The crystallized strip is placed on a multi-unit shelf using a 304 stainless steel tray. The thickness of a single tray is 6mm. The temperature entering the furnace is 80℃, and the temperature is raised to 580℃ at a rate of 4℃ / min and kept for 5h for heat treatment, so that boron can diffuse more evenly to the grain boundary, which is convenient for the subsequent chemical and physical driven particle separation. Step (6) Heat-treated strip material is crushed The ball mill is mixed with liquid nitrogen for ball milling. The grinding ball is made of zirconium oxide. Liquid nitrogen is added in a ratio of 1:2 for wet grinding and refining. The diameter distribution of the ball milled particles is controlled to be 0.3μm. The over-fine and over-coarse powders are removed and recycled. Step (7) Chemical and physical driven particle separation The ball mill particles were pickled for the first time, with the pickling solution being 1% acetic acid, the mass ratio of powder particles to pickling solution being 1:2, and pickling with stirring at 70°C for 10 minutes. After removing the upper layer of liquid, the primary pickling powder was obtained, and the broken nanoparticles were removed; the primary pickling mixture was pickled for the second time, with the pickling solution being 5% acetic acid, the mass ratio of powder particles to pickling solution being 1:5, and pickling with stirring at 85°C for 120 minutes with sufficient stirring; then, after repeated centrifugal washing and drying, the magnetic nanoparticles were obtained and collected.
[0018] The magnetic nanoparticles prepared in this example are single crystals, with more than 85% of the particles being free of damage, and more than 95% of the particles having a damage volume of ≤10%. The barium-based hexagonal particle size D80 is 25 nm, the particle shape is a hexagonal prism structure, the aspect ratio is 1.5:1, and the magnetic induction is 60 A·m 2 / kg, the TEM image of the prepared magnetic nanoparticles is shown in Figure 2 shown. Example 2
[0019] The present embodiment provides a method for preparing nanocrystalline strips and nanoparticles based on gas phase driving and liquid rolling, comprising the following steps: Step (1) Alloy melting Set the alloy composition by weight percentage to (Fe2O3) a (BaCO3) b (SrCO3) c (H3AlO3) d (H3BO3) e (CoO) f (TiO2) g (Bi2O3) h (Nd2O3) i , where the mass fractions are a: 30%; b: 40%; c: 5%; d: 2%; e: 15%; f: 1%; g: 1%; h: 3%; i: 3%; the melting crucible is made of high-purity alumina, heated to 1450°C for 3 hours, and then 1 / 3 of the weight of the molten powder is added to the alloy powder briquette after the alloy powder is melted; after it is completely melted, it is fully stirred for 40 minutes to promote uniform distribution; Step (2) Pouring After the alloy is melted and the crucible is preheated in place, the gate is heated online, and the molten alloy is poured into the distribution water outlet by using the method of water outlet flow storage, small diameter gate flow control and jet deposition ring injection, and the molten alloy is introduced through the water nozzle under the water outlet, and the liquid is dispersed into droplets through the jet deposition ring, and the droplets enter the roll gap of the double rollers for rolling and cooling; specifically, a preheater is used to preheat the water nozzle, wherein the water nozzle is made of alumina, the preheating temperature is 1300℃, the pouring water nozzle aperture is 2mm, the liquid level height is controlled at 150mm, and a weighing device is used to measure the amount of molten alloy, and the amount of molten alloy poured in and out is controlled; the water nozzle is located in the middle of the jet deposition ring, the water nozzle is aligned with the center line of the jet deposition ring, the lower plane of the water nozzle is parallel to the lower plane of the jet deposition ring, the distance between the jet deposition ring and the roll gap is 200mm, the slit width of the jet deposition ring is 2mm, the annular slit inclination angle is 45°, the focal length is 40mm, and the injection pressure is 0.3MPa; Step (3) Rolling Rolling process such as Figure 3 As shown, it includes a water nozzle 1, a spray deposition ring 2 and two casting rollers 3. When the molten liquid is poured, the double-roller roller surface rotates at a speed of 10m / s, and the double-roller arch frame moves back and forth along the axial direction as a whole, with a moving speed of 10mm / s, so as to facilitate the regulation of the heat exchange capacity of the roller surface; constant casting and rolling force control is adopted, and the sum of the casting and rolling forces on both sides is 100kN; the diameter of the casting roller is 300mm, the roller width is 200mm, and the roller surface convexity is ﹢15μm. According to the matching of the roller surface material and the casting roller stiffness, the roller gap is balanced after the casting and rolling force is applied; the casting roller material is beryllium copper chrome-plated, and the beryllium copper roller sleeve coating thickness is 100μm; the coating polishing roughness requirement is ≤Ra 0.8μm, and the hardness is ≥60HRC; the casting roller cooling water flux is 50m 3 / h; the casting roll power drive is directly connected to the servo motor to achieve synchronous dynamic adjustment; the width of the crystallized strip is controlled to be 30mm; Step (4) Collection of crystallized thin strips The casting machine outlet is designed with a multi-channel collecting bin to distinguish and collect the pouring, genuine product and cast residue separately. The cast residue bin is equipped with heat insulation materials to isolate it from the genuine product bin to avoid annealing influence. Step (5) Nanocrystallization diffusion heat treatment Take the genuine crystallized thin strip and carry out nano-crystallization diffusion heat treatment in an air-force circulation muffle furnace. The airflow velocity is 3m / s. The crystallized strip is placed on a multi-unit shelf using a 304 stainless steel tray. The thickness of a single tray is 6mm. The temperature entering the furnace is 80℃, and the temperature is raised to 620℃ at a rate of 4℃ / min and kept for 5h for heat treatment, so that boron can diffuse more evenly to the grain boundary, which is convenient for the subsequent chemical and physical driven particle separation. Step (6) Heat-treated strip material is crushed The ball mill is mixed with liquid nitrogen for ball milling. The grinding ball is made of zirconium oxide. Liquid nitrogen is added in a ratio of 1:2 for wet grinding and refining. The diameter distribution of the ball milled particles is controlled to be 0.3μm. The over-fine and over-coarse powders are removed and recycled. Step (7) Chemical and physical driven particle separation The ball mill particles were pickled for the first time, with the pickling solution being 1% acetic acid, the mass ratio of powder particles to pickling solution being 1:2, and pickling with stirring at 70°C for 10 minutes. After removing the upper layer of liquid, the primary pickling powder was obtained, and the broken nanoparticles were removed; the primary pickling mixture was pickled for the second time, with the pickling solution being 5% acetic acid, the mass ratio of powder particles to pickling solution being 1:5, and pickling with stirring at 85°C for 120 minutes with sufficient stirring; then, after repeated centrifugal washing and drying, the magnetic nanoparticles were obtained and collected.
[0020] The magnetic nanoparticles prepared in this example are single crystals, with more than 85% of the particles being free of damage, and more than 95% of the particles having a damage volume of ≤10%. The barium-based hexagonal particle size D80 is 20 nm, the particle shape is a hexagonal prism structure, the aspect ratio is 1.6:1, and the magnetic induction is 80 A·m 2 / kg. Example 3
[0021] The present embodiment provides a method for preparing nanocrystalline strips and nanoparticles based on gas phase driving and liquid rolling, comprising the following steps: Step (1) Alloy melting Set the alloy composition by weight percentage to (Fe2O3) a (BaCO3) b (SrCO3) c (H3AlO3) d (H3BO3) e (CoO) f (TiO2) g (Bi2O3) h (Nd2O3) i , where the mass fractions are a: 30%; b: 5%; c: 30%; d: 2%; e: 25%; f: 1%; g: 1%; h: 3%; i: 3%; the melting crucible is made of high-purity alumina, heated to 1450℃ and kept warm for 3 hours, and after the alloy powder is melted, 1 / 3 of the weight of the melted powder is added to the alloy powder briquette; after it is completely melted, it is fully stirred for 40 minutes to promote uniform distribution; Step (2) Pouring After the alloy is melted and the crucible is preheated in place, the gate is heated online, and the molten alloy is poured into the distribution water outlet by using the method of water outlet flow storage, small diameter gate flow control and jet deposition ring injection, and the molten alloy is introduced through the water nozzle under the water outlet, and the liquid is dispersed into droplets through the jet deposition ring, and the droplets enter the roll gap of the double rollers for rolling and cooling; specifically, a preheater is used to preheat the water nozzle, wherein the water nozzle is made of alumina, the preheating temperature is 1300℃, the pouring water nozzle aperture is 2mm, the liquid level height is controlled at 150mm, and a weighing device is used to measure the amount of molten alloy, and the amount of molten alloy poured in and out is controlled; the water nozzle is located in the middle of the jet deposition ring, the water nozzle is aligned with the center line of the jet deposition ring, the lower plane of the water nozzle is parallel to the lower plane of the jet deposition ring, the distance between the jet deposition ring and the roll gap is 200mm, the slit width of the jet deposition ring is 2mm, the annular slit inclination angle is 45°, the focal length is 40mm, and the injection pressure is 0.3MPa; Step (3) Rolling Rolling process such as Figure 3 As shown, it includes a water nozzle 1, a spray deposition ring 2 and two casting rollers 3. When the molten liquid is poured, the double-roller roller surface rotates at a speed of 10m / s, and the double-roller arch frame moves back and forth along the axial direction as a whole, with a moving speed of 10mm / s, so as to facilitate the regulation of the heat exchange capacity of the roller surface; constant casting and rolling force control is adopted, and the sum of the casting and rolling forces on both sides is 100kN; the diameter of the casting roller is 300mm, the roller width is 200mm, and the roller surface convexity is ﹢15μm. According to the matching of the roller surface material and the casting roller stiffness, the roller gap is balanced after the casting and rolling force is applied; the casting roller material is beryllium copper chrome-plated, and the beryllium copper roller sleeve coating thickness is 100μm; the coating polishing roughness requirement is ≤Ra 0.8μm, and the hardness is ≥60HRC; the casting roller cooling water flux is 50m 3 / h; the casting roll power drive is directly connected to the servo motor to achieve synchronous dynamic adjustment; the width of the crystallized strip is controlled to be 30mm; Step (4) Collection of crystallized thin strips The casting machine outlet is designed with a multi-channel collecting bin to distinguish and collect the pouring, genuine product and cast residue separately. The cast residue bin is equipped with heat insulation materials to isolate it from the genuine product bin to avoid annealing influence. Step (5) Nanocrystallization diffusion heat treatment Take the genuine crystallized thin strip and carry out nano-crystallization diffusion heat treatment in an air-force circulation muffle furnace. The airflow velocity is 3m / s. The crystallized strip is placed on a multi-unit shelf using a 304 stainless steel tray. The thickness of a single tray is 6mm. The temperature entering the furnace is 80℃, and the temperature is raised to 620℃ at a rate of 4℃ / min and kept for 5h for heat treatment, so that boron can diffuse more evenly to the grain boundary, which is convenient for the subsequent chemical and physical driven particle separation. Step (6) Heat-treated strip material is crushed The ball mill is mixed with liquid nitrogen for ball milling. The grinding ball is made of zirconium oxide. Liquid nitrogen is added in a ratio of 1:2 for wet grinding and refining. The diameter distribution of the ball milled particles is controlled to be 0.3μm. The over-fine and over-coarse powders are removed and recycled. Step (7) Chemical and physical driven particle separation The ball mill particles were pickled for the first time, with the pickling solution being 1% acetic acid, the mass ratio of powder particles to pickling solution being 1:2, and pickling with stirring at 70°C for 10 minutes. After removing the upper layer of liquid, the primary pickling powder was obtained, and the broken nanoparticles were removed; the primary pickling mixture was pickled for the second time, with the pickling solution being 5% acetic acid, the mass ratio of powder particles to pickling solution being 1:5, and pickling with stirring at 85°C for 120 minutes with sufficient stirring; then, after repeated centrifugal washing and drying, the magnetic nanoparticles were obtained and collected.
[0022] The magnetic nanoparticles prepared in this example are single crystals, with more than 85% of the particles being free of damage, and more than 95% of the particles having a damage volume of ≤10%. The strontium-based hexagonal particle size D80 is 10 nm, the particle shape is a hexagonal prism structure, the aspect ratio is 1.5:1, and the magnetic induction is 60 A·m 2 / kg. Example 4
[0023] The present embodiment provides a method for preparing nanocrystalline strips and nanoparticles based on gas phase driving and liquid rolling, comprising the following steps: Step (1) Alloy melting Set the alloy composition by weight percentage to (Fe2O3) a (BaCO3) b (SrCO3) c (H3AlO3) d (H3BO3) e (CoO) f (TiO2) g (Bi2O3) h (Nd2O3) i , where the mass fractions are a: 30%; b: 5%; c: 40%; d: 2%; e: 15%; f: 1%; g: 1%; h: 3%; i: 3%; the melting crucible is made of high-purity alumina (, heated to 1450℃ for 3 hours, and then the alloy powder is melted and then 1 / 3 of the weight of the melted powder is added to the alloy powder briquette; after it is completely melted, it is fully stirred for 40 minutes to promote uniform distribution; Step (2) Pouring After the alloy is melted and the crucible is preheated in place, the gate is heated online, and the molten alloy is poured into the distribution water outlet by using the method of water outlet flow storage, small diameter gate flow control and jet deposition ring injection, and the molten alloy is introduced through the water nozzle under the water outlet, and the liquid is dispersed into droplets through the jet deposition ring, and the droplets enter the roll gap of the double rollers for rolling and cooling; specifically, a preheater is used to preheat the water nozzle, wherein the water nozzle is made of alumina, the preheating temperature is 1300℃, the pouring water nozzle aperture is 2mm, the liquid level height is controlled at 150mm, and a weighing device is used to measure the amount of molten alloy, and the pouring and pouring amount of molten alloy is controlled; the water nozzle is located in the middle of the jet deposition ring, the water nozzle is aligned with the center line of the jet deposition ring, the lower plane of the water nozzle is parallel to the lower plane of the jet deposition ring, the distance between the jet deposition ring and the roll gap is 200mm, the slit width of the jet deposition ring is 2mm, the annular slit inclination angle is 45°, the focal length is 40mm, and the injection pressure is 0.3MPa; Step (3) Rolling Rolling process such as Figure 3 As shown, it includes a water nozzle 1, a spray deposition ring 2 and two casting rollers 3. When the molten liquid is poured, the double-roller roller surface rotates at a speed of 10m / s, and the double-roller arch frame moves back and forth along the axial direction as a whole, with a moving speed of 10mm / s, so as to facilitate the regulation of the heat exchange capacity of the roller surface; constant casting and rolling force control is adopted, and the sum of the casting and rolling forces on both sides is 100kN; the diameter of the casting roller is 300mm, the roller width is 200mm, and the roller surface convexity is ﹢15μm. According to the matching of the roller surface material and the casting roller stiffness, the roller gap is balanced after the casting and rolling force is applied; the casting roller material is beryllium copper chrome-plated, and the beryllium copper roller sleeve coating thickness is 100μm; the coating polishing roughness requirement is ≤Ra 0.8μm, and the hardness is ≥60HRC; the casting roller cooling water flux is 50m 3 / h; the casting roll power drive is directly connected to the servo motor to achieve synchronous dynamic adjustment; the width of the crystallized strip is controlled to be 30mm; Step (4) Collection of crystallized thin strips The casting machine outlet is designed with a multi-channel collecting bin to distinguish and collect the pouring, genuine product and cast residue separately. The cast residue bin is equipped with heat insulation materials to isolate it from the genuine product bin to avoid annealing influence. Step (5) Nanocrystallization diffusion heat treatment Take the genuine crystallized thin strip and carry out nano-crystallization diffusion heat treatment in an air strong circulation muffle furnace. The air flow velocity is 3m / s. The crystallized strip is placed on a multi-unit shelf using a 304 stainless steel tray. The thickness of a single tray is 6mm. The temperature entering the furnace is 80℃, and the temperature is raised to 670℃ at a rate of 4℃ / min and kept for 5h for heat treatment, so that boron can diffuse more evenly to the grain boundary, which is convenient for the subsequent chemical and physical driven particle separation. Step (6) Heat-treated strip material is crushed The ball mill is mixed with liquid nitrogen for ball milling. The grinding ball is made of zirconium oxide. Liquid nitrogen is added in a ratio of 1:2 for wet grinding and refining. The diameter distribution of the ball milled particles is controlled to be 0.3m. The over-fine and over-coarse powders are removed and recycled. Step (7) Chemical and physical driven particle separation The ball mill particles were pickled for the first time, with the pickling solution being 1% acetic acid, the mass ratio of powder particles to pickling solution being 1:2, and pickling with stirring at 70°C for 10 minutes. After removing the upper layer of liquid, the primary pickling powder was obtained, and the broken nanoparticles were removed; the primary pickling mixture was pickled for the second time, with the pickling solution being 5% acetic acid, the mass ratio of powder particles to pickling solution being 1:5, and pickling with stirring at 85°C for 120 minutes with sufficient stirring; then, after repeated centrifugal washing and drying, the magnetic nanoparticles were obtained and collected.
[0024] The magnetic nanoparticles prepared in this example are single crystals, with more than 85% of the particles being free of damage, and more than 95% of the particles having a damage volume of ≤10%. The strontium-based hexagonal particle size D80 is 8 nm, the particle shape is a hexagonal prism structure, the aspect ratio is 1.3:1, and the magnetic induction is 70 A·m 2 / kg.
Claims
1. A method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling, characterized in that: The following steps are involved: Step (1) Alloy melting Smelt the alloy according to the set composition. Use high-purity alumina or Pt-Rh alloy in the smelting crucible. Heat it to 1300-1450℃ and keep it warm for 2-3 hours. After the alloy powder is melted, add 1 / 3 of the weight of the melted powder into the alloy powder briquette. After it is completely melted, stir it for more than 30 minutes to promote uniform distribution. Step (2) Pouring After the alloy is melted and the crucible is preheated, the gate is heated online, and the molten alloy is poured into the distribution nozzle by using the method of water gate flow storage, small diameter gate flow control and spray deposition ring spraying. The molten alloy is introduced through the nozzle down nozzle, and the liquid is dispersed into droplets through the spray deposition ring. The droplets enter the double-roll gap for rolling and cooling; Step (3) Rolling During the rolling process, when the molten liquid is poured, the double-roller surface speed is 2-10m / s, and the double-roller arch frame moves back and forth along the axial direction as a whole, with a moving speed of 0~20mm / s, which is convenient for adjusting the heat exchange capacity of the roller surface; constant casting and rolling force control is adopted, and the sum of the casting and rolling forces on both sides is 10-100kN; the diameter of the casting roller is 200-400mm, the roller width is 110-350mm, and the roller surface convexity is +10~25μm. According to the matching of the roller surface material and the casting roller stiffness, after the casting and rolling force is applied, the roller gap is balanced; the cooling water flux of the casting roller is 30-100m 3 / h; the casting roll power drive is directly connected to the servo motor to achieve synchronous dynamic adjustment; the width of the crystallized strip is controlled to be 5~40mm; Step (4) Collection of crystallized thin strips The casting machine outlet is designed with a multi-channel collecting bin to distinguish and collect the pouring, genuine product and cast residue separately. The cast residue bin is equipped with heat insulation materials to isolate it from the genuine product bin to avoid annealing influence. Step (5) Nanocrystallization diffusion heat treatment Take the genuine crystallized thin ribbon and carry out nano-crystallization diffusion heat treatment in a strong air circulation muffle furnace to make the boron diffuse more evenly to the grain boundary, which is convenient for the subsequent chemical and physical driven particle separation; Step (6) Heat-treated strip material is crushed The ball mill is mixed with liquid nitrogen for ball milling. The grinding ball is made of zirconium oxide or titanium oxide. Liquid nitrogen is added in a ratio of 1:2 for wet grinding and refining. The diameter distribution of the ball milled particles is controlled to be 0.1~0.5μm. The over-fine and over-coarse powders are removed and recycled. Step (7) Chemical and physical driven particle separation The ball mill particles are subjected to the first pickling, the pickling solution is 1% acetic acid, the mass ratio of powder particles to pickling solution is 1:2~4, and the pickling is stirred at 70°C for 5~10 minutes. After removing the upper liquid, the primary pickling powder is obtained, and the broken nanoparticles are removed; the primary pickling mixture is subjected to the second pickling, the pickling solution is 5% acetic acid, the mass ratio of powder particles to pickling solution is 1:5~10, and the pickling is stirred at 85°C for 100-150 minutes with sufficient stirring; then after repeated centrifugal washing and drying, the magnetic nanoparticles are obtained and collected.
2. The method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling according to claim 1, characterized in that: The set composition in step (1) is (Fe2O3) by weight percentage. a (BaCO3) b (SrCO3) c (H3AlO3) d (H3BO3) e (CoO) f (TiO2) g (Bi2O3) h (Nd2O3) i , where mass fraction a: 10~30%; b: 30~40% or 1~6%; c: 1~5% or 30~40%; d: 0~3%; e:10~25%; f:0~1%; g:0~1%; h:0~5%; i:0~5%。 3. A method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling according to claim 1, characterized in that: In step (2), a preheater is used to preheat a water nozzle, wherein the water nozzle is made of alumina or Pt-Rh, the preheating temperature is 1200-1300°C, the pouring water nozzle aperture is 1-3mm, the liquid level height is controlled at 100-180mm, a weighing device is used to measure the amount of molten alloy, and the pouring in and out amount of molten alloy is controlled; the water nozzle is located in the middle of the jet deposition ring, the water nozzle is aligned with the center line of the jet deposition ring, the lower plane of the water nozzle is parallel to the lower plane of the jet deposition ring, the jet deposition ring is 200-240mm away from the roller gap, the slit width of the jet deposition ring is 1-2mm, the annular slit inclination angle is 45°, the focal length is 40mm, and the injection pressure is 0.3-0.4MPa.
4. The method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling according to claim 1, characterized in that: In step (3), the casting roller is made of beryllium copper or chrome-plated die steel, wherein the coating thickness of the beryllium copper roller sleeve is 50-250 μm, and the coating thickness of the die steel chrome-plated sleeve is 10-50 μm, and the coating polishing roughness requirements are both ≤Ra0.8 μm, and the hardness is both ≥60HRC.
5. The method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling according to claim 1, characterized in that: The heat treatment process in step (5) is as follows: the air flow velocity is 2-3 m / s, the crystallized strip is placed on a multi-unit shelf using a 304 stainless steel tray, and the thickness of a single tray does not exceed 10 mm; the temperature entering the furnace is not higher than 100°C, and the temperature is raised to 550-790°C at a rate of ≤10°C / min and maintained at this temperature for 0.5-5h for heat treatment.
6. The method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling according to claim 1, characterized in that: The nanoparticles prepared by this preparation method are single crystals, with more than 85% of the particles being undamaged, the damaged volume being ≤10%, and the particle proportion being more than 95%.
7. The method for preparing nanocrystalline strips and nanoparticles based on gas phase drive and liquid rolling according to claim 1, characterized in that: The strontium-based and barium-based nanoparticles prepared by the preparation method have a particle size D80 of 8-10 nm and 20-30 nm in six directions, a particle shape of a hexagonal prism structure, an aspect ratio of 1.2-1.8:1, and a magnetic induction of 35-80 A·m 2 / kg.
Citation Information
Patent Citations
High-silicon-steel thin belt and preparation method thereof
CN101935800A
Method for preparing high-silicon electric steel band material through rolling at medium and low temperature
CN102605153A
Method for manufacturing iron-base soft magnetic alloy
CN1172862A